2018
DOI: 10.1007/s10534-018-0088-4
|View full text |Cite
|
Sign up to set email alerts
|

Antirotaviral potential of lactoferrin from different origin: effect of thermal and high pressure treatments

Abstract: Rotaviral gastroenteritis causes a high rate of infant mortality and severe healthcare implications worldwide. Several studies have pointed out that human milk and dairy fractions, such as whey and buttermilk, possess antirotaviral activity. This activity has been mainly associated with glycoproteins, among them lactoferrin (LF). Thermal treatments are necessary to provide microbiological safety and extend the shelf life of milk products, though they may diminish their biological value. High hydrostatic pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Parrón et al [38] reported similar protein profile and lactose and protein contents for cow and sheep buttermilk, but higher lipid content for the latter. The same group [38][39][40] reported a higher dosedependent antiviral activity of sheep buttermilk and its components compared with its cow counterpart. The gross composition and cheese making potential of sweet sheep and goat buttermilk alone or in mixtures with milk with variable fat content has been investigated by Sakkas et al [24].…”
Section: Introductionmentioning
confidence: 97%
“…Parrón et al [38] reported similar protein profile and lactose and protein contents for cow and sheep buttermilk, but higher lipid content for the latter. The same group [38][39][40] reported a higher dosedependent antiviral activity of sheep buttermilk and its components compared with its cow counterpart. The gross composition and cheese making potential of sweet sheep and goat buttermilk alone or in mixtures with milk with variable fat content has been investigated by Sakkas et al [24].…”
Section: Introductionmentioning
confidence: 97%
“…17,20 However, the same antiviral activity against Rotavirus has been observed for bovine Lf, in both native and holo forms. 21 Several assays have also shown that, depending on iron saturation, Lf displays divergent effects on the growth of probiotic bacteria. 17 The capacity of bLf to modulate the gut microbiota positively has been previously demonstrated in high-fat diet induced obese mice, 22 dextran sulfate sodium induced colitis model 23 or Alzheimer's disease models.…”
Section: Introductionmentioning
confidence: 99%
“…Although we observed no anti-HAV activity, it is possible that other non-enveloped viruses could be partially inactivated by human milk. In fact, previous studies have demonstrated that human milk can partially inactivate rotavirus, a non-enveloped virus; further evidence is needed to examine other non-enveloped viruses ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%